(untitled) (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
Background. Kardola Village in Sambalpur district, Odisha-formally adopted by Odisha State Open University (OSOU) under the Unnat Bharat Abhiyan (UBA)-comprises forty-five weaving households (142 members) whose livelihoods depend on the production of Sambalpuri Ikat (Bandha) handloom sarees. Field data indicate monthly household incomes of ₹4,500-₹8,000, with variation driven largely by differential market access rather than craft quality. Because nearly all output is sold through local trader intermediaries, weavers realise only a fraction of the eventual retail value of their products. Objective. This study documents the current production and marketing conditions of the Kardola weaving community and, on that empirical basis, develops and specifies the Handloom 4.0 framework: an AI-assisted, Direct-to-Customer (D2C) digital commerce model intended to reduce trader dependence and improve income realisation. Methods. A Participatory Design methodology was applied. Primary data were collected through a household census (N = 45), semi-structured interviews with primary earning members, four focus group discussions, structured observation of production and transaction practices, and iterative co-design workshops. Qualitative data were analysed using reflexive thematic analysis; quantitative baseline indicators were triangulated across interview, observation, and group-verification sources. The framework was refined through member checking and expert review. Findings. The baseline analysis indicates that income suppression is primarily a function of channel structure and credit dependence rather than production capacity, and that the community already possesses substantial latent digital assets (smartphone access in 38 of 45 households; active WhatsApp use in 36). The Handloom 4.0 framework is specified in five integrated layers: an AI-assisted product catalogue, WhatsApp-first social commerce, QR/UPI-based direct payment, aggregated community logistics, and a producer-company governance structure. Projected outcomes and limitations. Using an income model derived from observed price differentials, the framework is projected-under stated adoption and demand assumptions-to raise monthly household income toward ₹12,000-₹18,000 and to reduce trader dependence over an eighteen-month horizon. These figures are analytical projections rather than measured results; empirical validation through a controlled pilot is identified as the essential next stage. The study contributes a transferable, community-centred model for artisan D2C transformation while explicitly delineating its evidentiary boundaries.